Politeness, Power, and Identity in Podcast Discourse: an Emic Discursive Pragmatic Analysis of Digital Talk - Kristina Marta Noviance; R. Kunjana Rahardi (Aksara, 2026)
Podcast communication has evolved into a significant site of digital public discourse, where norms of politeness are no longer fixed but are continuously negotiated and redefined within dynamic interactions. This study aims to analyze politeness practices in podcast discourse by examining how politeness is constructed, interpreted, and negotiated in relation to power relations and identity formation among speakers. This research employs a qualitative design using an integrative discursive pragmatic approach grounded in an emic–epistemological perspective. The data consist of utterances from naturally occurring podcast interactions. The data sources are selected podcast episodes featuring interactions between hosts and guests. Data were collected through observation methods, employing recording and note-taking techniques. Data analysis was conducted using discursive pragmatic analysis, involving data reduction, categorization of politeness strategies, interpretation of interactional and sociocultural contexts, and meaning-making based on participants’ emic perspectives. The findings reveal that politeness in podcast discourse functions not only to maintain interpersonal harmony but also to assert authority, expertise, and social identity. Speakers with higher symbolic power tend to control interactional norms, while less dominant participants adjust their politeness strategies accordingly. Furthermore, discrepancies between actual politeness practices and conventional theoretical models indicate that politeness is highly contextual and dynamic within digital environments. The implications of this study highlight the need to develop more context-sensitive and adaptive politeness theories in digitally mediated communication, particularly within discursive pragmatics. This research also contributes to fostering more inclusive communication practices and opens avenues for further studies across diverse podcast genres, marginalized speaker groups, and cross-cultural contexts. AbstrakKomunikasi podcast telah berkembang menjadi ruang penting dalam wacana publik digital, di mana norma kesantunan tidak lagi bersifat tetap, melainkan dinegosiasikan dan didefinisikan ulang dalam interaksi yang dinamis. Penelitian ini bertujuan untuk menganalisis praktik kesantunan dalam wacana podcast dengan menyoroti bagaimana kesantunan dikonstruksi, ditafsirkan, dan dinegosiasikan dalam kaitannya dengan relasi kekuasaan dan pembentukan identitas penutur. Penelitian ini merupakan penelitian kualitatif dengan pendekatan pragmatik diskursif integratif berbasis perspektif emik–epistemologis. Data penelitian berupa tuturan dalam interaksi podcast yang diperoleh dari rekaman podcast autentik (naturally occurring data). Sumber data berasal dari beberapa episode podcast yang memuat interaksi antara host dan narasumber. Teknik pengumpulan data dilakukan melalui metode simak dengan teknik rekam dan catat. Teknik analisis data menggunakan analisis pragmatik diskursif, dengan tahapan reduksi data, kategorisasi strategi kesantunan, interpretasi konteks interaksional dan sosiokultural, serta penafsiran makna berdasarkan perspektif emik partisipan. Hasil penelitian menunjukkan bahwa kesantunan dalam wacana podcast tidak hanya berfungsi menjaga keharmonisan interpersonal, tetapi juga menjadi sarana untuk menegaskan otoritas, keahlian, dan identitas sosial. Penutur dengan kekuasaan simbolik lebih tinggi cenderung mengontrol norma interaksi, sedangkan partisipan yang kurang dominan menyesuaikan strategi kesantunannya. Selain itu, ditemukan adanya perbedaan antara praktik kesantunan aktual dengan model teoretis konvensional, yang menunjukkan bahwa kesantunan bersifat kontekstual dan dinamis dalam ruang digital. Implikasi penelitian ini menegaskan pentingnya pengembangan teori kesantunan yang lebih kontekstual dan adaptif terhadap media digital, khususnya dalam kajian pragmatik diskursif. Penelitian ini juga memberikan kontribusi bagi pengembangan praktik komunikasi yang lebih inklusif serta membuka peluang penelitian lanjutan pada berbagai genre podcast, kelompok marjinal, dan konteks lintas budaya.